2014
DOI: 10.1073/pnas.1319742111
|View full text |Cite
|
Sign up to set email alerts
|

Functional and genetic studies of isolated cells from parathyroid tumors reveal the complex pathogenesis of parathyroid neoplasia

Abstract: Significance Parathyroid adenomas, the main cause of primary hyperparathyroidism (PHPT), are thought to result from clonal expansion of tumor cells and to be insensitive to normal calcium feedback due to the loss of the calcium-sensing receptor (CASR). Utilizing flow cytometric analysis to isolate and individually study oxyphil cells, chief cells, and lymphocytes from resected parathyroid tumors and glands, we now report previously unrecognized heterogeneity in these tissues with respect to calcium r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 26 publications
4
41
2
Order By: Relevance
“…With the rise of circulating calcium levels, a classic endocrine feedback loop occurs, whereby the CaSRs and its signalling pathway are reactivated, silencing PTH secretion 7 33 80 141 168 169. In HPT, various alterations inactivating CaSR signalling pathway can occur, causing excess PTH secretion 7 11 13 33 42 78 81 141 166. Furthermore, if downregulation of CaSR persists over time, studies have shown that it can lead to aberrant cell growth and proliferation (thought to be related to aberrant Wnt/β-catenin and cyclin D1 signalling), suggesting that CaSR signalling may serve a tumour suppressor function in the parathyroid glands 7 11 33 42 78 81 141 152 166 170–172…”
Section: Pathogenesis and Molecular Genetics Of Hptmentioning
confidence: 99%
“…With the rise of circulating calcium levels, a classic endocrine feedback loop occurs, whereby the CaSRs and its signalling pathway are reactivated, silencing PTH secretion 7 33 80 141 168 169. In HPT, various alterations inactivating CaSR signalling pathway can occur, causing excess PTH secretion 7 11 13 33 42 78 81 141 166. Furthermore, if downregulation of CaSR persists over time, studies have shown that it can lead to aberrant cell growth and proliferation (thought to be related to aberrant Wnt/β-catenin and cyclin D1 signalling), suggesting that CaSR signalling may serve a tumour suppressor function in the parathyroid glands 7 11 33 42 78 81 141 152 166 170–172…”
Section: Pathogenesis and Molecular Genetics Of Hptmentioning
confidence: 99%
“…Western blot was performed as previously described [19] . Anti-extracellular regulated kinase (ERK) 1/2, anti-phospho-ERK1/2, anti-β-actin and horseradish peroxidase-conjugated anti-IgG were purchased from Cell Signaling Technology (Danvers, Mass., USA).…”
Section: Western Blotmentioning
confidence: 99%
“…Forty-eight hours later, cells were harvested, homogenized, and subjected to Western blot analysis of Piezo1 protein expression following the previous protocol [16]. Briefly, the treated HUVECs were homogenized in lysis buffer (1% SDS, 10 mM Tris pH 8.0, 130 mM NaCl, 5 mM EDTA) containing protease inhibitors.…”
Section: Western Blot Of Piezo1 Protein Expressionmentioning
confidence: 99%